Application Of Ordinal Logistic Regression On Harmonious Religion Communion Data In Bali Province In 2024 - Al-Imdi, Fourria Renggani; Khikmah, Laelatul (JURNAL SINTAK, 2025)
This study aims to analyze the influence of educational attainment and income level on the Religious Harmony Index in Bali Province using ordinal logistic regression. Secondary data from the 2024 Religious Harmony Survey was used, involving 400 respondents. The research results indicate that neither education nor income has a significant effect on the level of religious harmony in Bali Province. This suggests that structural factors such as education and economy may not be the primary determinants of social harmony in Balinese society, but rather cultural values, local wisdom, and social interactions that have been internalized in daily life. The simultaneous test results show that the overall ordinal logistic regression model is not significant. This conclusion affirms that harmony in Bali is influenced by factors other than the variables tested.